Determination of HIV Status in African Adults With Discordant HIV Rapid Tests - Fogel, Jessica M; Piwowar-Manning, Estelle; Donohue, Kelsey; Cummings, Vanessa; Marzinke, Mark A; Clarke, William; Breaud, Autumn; Fiamma, Agnès; Donnell, Deborah; Kulich, Michal; Mbwambo, Jessie K K; Richter, Linda; et al. (Journal of acquired immune deficiency syndromes (1999), 2015)
BACKGROUND: In resource-limited settings, HIV infection is often diagnosed using 2 rapid tests. If the results are discordant, a third tie-breaker test is often used to determine HIV status. This study characterized samples with discordant rapid tests and compared different testing strategies for determining HIV status in these cases. METHODS: Samples were previously collected from 173 African adults in a population-based survey who had discordant rapid test results. Samples were classified as HIV positive or HIV negative using a rigorous testing algorithm that included two fourth-generation tests, a discriminatory test, and 2 HIV RNA tests. Tie-breaker tests were evaluated, including rapid tests (1 performed in-country), a third-generation enzyme immunoassay, and two fourth-generation tests. Selected samples were further characterized using additional assays. RESULTS: Twenty-nine samples (16.8%) were classified as HIV positive and 24 of those samples (82.8%) had undetectable HIV RNA. Antiretroviral drugs were detected in 1 sample. Sensitivity was 8.3%-43% for the rapid tests; 24.1% for the third-generation enzyme immunoassay; 95.8% and 96.6% for the fourth-generation tests. Specificity was lower for the fourth-generation tests than the other tests. Accuracy ranged from 79.5% to 91.3%. CONCLUSIONS: In this population-based survey, most HIV-infected adults with discordant rapid tests were virally suppressed without antiretroviral drugs. Use of individual assays as tie-breaker tests was not a reliable method for determining HIV status in these individuals. More extensive testing algorithms that use a fourth-generation screening test with a discriminatory test and HIV RNA test are preferable for determining HIV status in these cases.
Keywords: HIV Antibodies; Sensitivity and Specificity; senzitivita a specificita; Humans; HIV infekce; HIV protilátky; HIV Infections; dospělí; lidé; Tanzanie; časové faktory; HIV antigeny; Adult; Immunoassay; South Africa; Tanzania; HIV Antigens; Jihoafrická republika; imunoanalýza; Time Factors